Penilaian Sikap llmiah Dalam Pembelajaran Sains - Anwar, Herson (Jurnal Pelangi Ilmu, 2009)
Assessment of scientific attitude in science study,important is executed along of in study of science relates to abiliti, causing becomes solvent student referance or inabiliti at study. Attitude contains three dimensions namely cognate trust, feeling of akfektif or evaluatif and behavior of someone to attitude object. Assessment result of learning Sains is assumed complete if including cognate aspect, affective, and psikomotor. Attitude is bahaviour having the character of public disseminating is thin is of all thing done by student. But attitude also is one other having an in with result of student learning. Distinguishable scientific attitude from simply attitude to Sains, because attitude to Sains only be focused at does student like or doesnt́ like to study Sains. Of course positive attitude to study of Sains will give high contribution in forming of scientific attitude of student.